2012
DOI: 10.1371/journal.pone.0039777
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of MicroRNA Gene Polymorphisms on the Susceptibility of Environmental Factors Leading to Carcinogenesis in Oral Cancer

Abstract: Background MicroRNAs (miRNAs) have been regarded as a critical factor in targeting oncogenes or tumor suppressor genes in tumorigenesis. The genetic predisposition of miRNAs-signaling pathways related to the development of oral squamous cell carcinoma (OSCC) remains unresolved. This study examined the associations of polymorphisms with four miRNAs with the susceptibility and clinicopathological characteristics of OSCC. Methodology/Principal Findings A total of 895 male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 38 publications
4
69
1
1
Order By: Relevance
“…One study was excluded as it was not associated with hsa-mir-499 rs3746444 A>G (Kupcinskas et al, 2012). After further excluding two abstracts (Hu et al, 2009;Hwang et al, 2010), thirty-nine case-control studies involving 14,136 cases and 16,937 controls were selected for meta-analysis (Hu et al, 2009;Tian et al, 2009;Catucci et al, 2010;Liu et al, 2010;Okubo et al, 2010;Srivastava et al, 2010;Akkiz et al, 2011;George et al, 2011;Ling et al, 2011;Mittal et al, 2011;Vinci et al, 2011;Zhou et al, 2011;Alshatwi et al, 2012;Chu et al, 2012;Kim et al, 2012;Min et al, 2012;Xiang et al, 2012;Zhou et al, 2012;Ahn et al, 2013;Lv et al, 2013;Shan et al, 2013;Song et al, 2013;Umar et al, 2013;Vinci et al, 2013;Wei et al, 2013;Wu et al, 2013;Zou and Zhao, 2013;Bansal et al, 2014;Chu et al, 2014;Du et al, 2014;Gutierrez-Camino et al, 2014;Hasani et al, 2014;Hou et al, 2014;Hu et al, 2014;Ma et al, 2014;Omrani et al, 2014;Pu et ...…”
Section: Methodsmentioning
confidence: 99%
“…One study was excluded as it was not associated with hsa-mir-499 rs3746444 A>G (Kupcinskas et al, 2012). After further excluding two abstracts (Hu et al, 2009;Hwang et al, 2010), thirty-nine case-control studies involving 14,136 cases and 16,937 controls were selected for meta-analysis (Hu et al, 2009;Tian et al, 2009;Catucci et al, 2010;Liu et al, 2010;Okubo et al, 2010;Srivastava et al, 2010;Akkiz et al, 2011;George et al, 2011;Ling et al, 2011;Mittal et al, 2011;Vinci et al, 2011;Zhou et al, 2011;Alshatwi et al, 2012;Chu et al, 2012;Kim et al, 2012;Min et al, 2012;Xiang et al, 2012;Zhou et al, 2012;Ahn et al, 2013;Lv et al, 2013;Shan et al, 2013;Song et al, 2013;Umar et al, 2013;Vinci et al, 2013;Wei et al, 2013;Wu et al, 2013;Zou and Zhao, 2013;Bansal et al, 2014;Chu et al, 2014;Du et al, 2014;Gutierrez-Camino et al, 2014;Hasani et al, 2014;Hou et al, 2014;Hu et al, 2014;Ma et al, 2014;Omrani et al, 2014;Pu et ...…”
Section: Methodsmentioning
confidence: 99%
“…In accordance with the inclusion criteria, 21 eligible studies including 20 published (Xu et al, 2008;Zeng et al, 2010;Okubo et al, 2010;Srivastava et al, 2010;Guo et al, 2010;Akkız et al, 2011;Zhang et al, 2011;Ahn et al, 2012;Chu et al, 2012;Hezova et al, 2012;Mihalache et al, 2012;Xiang et al, 2012;Zhou et al, 2012;Zhou et al, 2012;Min et al, 2012;Kim et al, 2012;Chae et al, 2013;Hu et al, 2013;Lv et al, 2013;Ma et al, 2013;Pavlakis et al, 2013;Wei et al, 2013) and 1 unpublished were collected in this work, with 9,558 cases and 10,614 controls. Two study identified by manually searching reference list of retrieved studies were included (Chu et al, 2012;Kim et al, 2012).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Two study identified by manually searching reference list of retrieved studies were included (Chu et al, 2012;Kim et al, 2012). The Figure 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…76 Furthermore, there was a significant association between SNPs of these four miRNA genes and an increased risk of OSCC associated with betel nut chewers and smokers. 77 As the genes encoding miRNAs are frequently located in fragile sites, it is plausible that loss or gain of chromosomal material could alter miRNA expression. 78 For instance, the expression of miR-100 and miR-125b, two miRNAs mapping to chromosome 11q, is significantly decreased in OSCC owing to the loss of chromosome material.…”
Section: Mirnas In Oscc-mechanisms Of Deregulationmentioning
confidence: 99%